Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 9: First-Order Differential Equations - Section 9.5 - Systems of Equations and Phase Planes - Exercises 9.5 - Page 557: 14



Work Step by Step

Here, we have $y'+y=4(xe^x)$ The integrating factor is: $I=e^{\int (1) dx}=e^{x}$ Now, $(e^{x})[y'+y]=4(xe^x)(e^{x})$ This implies that $\int [e^{x}y]' =\int 4xe^{2x} dx $ $\implies e^{x}y=(2x)(e^{2x})-e^{x}+c$ Hence, $y=(2x)(e^{x})-e^{x}+ce^{-x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.